A source‐sink model for water diffusion in an activated carbon fiber/phenolic composite. Issue 7 (24th May 2021) - Alston, Sue; Arnold, Cris; Swan, Martin; Stone, Corinne
Abstract: The moisture absorption behavior of a composite comprising phenolic resin and activated carbon fibers was characterized. The resin starts with a water content from curing and the active fibers both adsorb water on their surface and absorb water in sub‐surface pores, acting as a sink or source of water. Measured data showed that the dependence of this water uptake on the surrounding relative humidity was highly nonlinear, and that the effective diffusion rate through the composite was very dependent on the starting and end conditions. A physically based model has been successfully developed to simulate this behavior. Diffusion was assumed to be Fickian and entirely through the resin, with a linear dependence of resin water content on external humidity. Water movement between resin and fibers was determined so as to maintain equilibrium, based on measured steady‐state water uptake curves across a range of relative humidities. This meant that in mid‐range humidities, most water movement was between fibers and resin rather than through the resin, giving low effective diffusion rates. This model and a simple Arrhenius expression for the diffusion coefficient through the resin enabled measured composite diffusion behavior to be accurately predicted over a range of temperatures and humidity changes. Abstract : During moisture absorption by a composite comprising phenolic resin and activated carbon fibers, the active fibers both adsorb water on their surface and absorb water in subsurface pores, acting as a sink or source of water. A model has been successfully developed to simulate this behavior, allowing accurate prediction of measured composite diffusion over a range of temperatures and humidity changes.